Between-gender differences in trunk rotational power in athletes of gymnastic and dance sports - Zemkova, E.; Kyselovicova, O.; Jelen, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: A previous study revealed sport-specific differences in power-velocity-force profiling during trunk rotations at loads =10.5 kg [1]. The highest power is produced by combat sports athletes (boxing, thai boxing, karate, tae kwon do) with a maximum achieved at 10.5 kg, followed by water sports athletes (canoeing, kayaking) with a maximum at 20.0 kg, grappling sports athletes (judo, wrestling) with a maximum at 15.5 kg, and ball sports athletes (golf, hockey, tennis) with a maximum at 10.5 kg [1]. Since body rotations represent one of the essential elements of performance also in gymnasts and dancers, we were interested in whether between-gender differences exist in trunk rotational power at various loads.